Exergetic issues of thermoregulation physiology in different climates. (2015) - Dovjak, Mateja; Shukuya, Masanori; Krainer, Aleš
The purpose of the paper is to analyse the physiology of thermoregulation in various climate types using human body exergy balance model where mutual influence of environmental parameters and personal factors are considered. Two virtual persons with different metabolic rates and effective clothing insulations were exposed to selected climate conditions. Human body exergy balance (hBExB) was calculated with software developed by Hideo Asada Rev 2010. Results showed that climate conditions in combination with metabolic rate and effective clothing insulation had large influence on every part of hBExB. Thermally comfortable conditions with PMV index closer to 0 did not always result in the lowest possible hbExC rate. The value of hbExC rate strongly depends on environmental parameters as well as on metabolic rate and effective clothing insulation. Understanding the mutual influence of environmental parameters and personal factors on hBExB is a key factor for identifying recommendations for healthy, comfortable and stimulative conditions.